Why is Popper's critical method fascinating? - Polak, Paweł Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
This review article presents an important, newly published study of Popper's critical method by Zbigniew Liana. The review emphasizes the very high level of the study, points to its originality, and explains why the book is recommended mainly to specialists of Popper's thought. It is also explained how the book manages to contain so many original and valuable analyses in a small volume.
Keywords: Fries's trilemma; critical philosophy; critical method; transcendetal method; philosophy of science; metaphilosophy; Karl Popper; Leonard Nelson; Jakob Friedrich Fries; Immanuel Kant